Tratamiento informativo realizado por las ediciones digitales komsomolskaya pravda, el país, the new york times y the sun, sobre la detención de Julian Assange, abril – septiembre 2019. - Jessica Gissel, Trujillo Mero (2020)
The present investigation emerged to identify the informative treatment carried out by the digital editions. Such Komsomolskaya Pravda, El País, The New York Times and The Sun on the arrest of Julian Assange, in the period April, September 2019, considering that the act of apprehension of the Australian occurred in April, giving since a change to his condition. It worked with scientific, historical, logical, inductive, analytical and descriptive methods. The research is qualitative and quantitative, since we investigated what it says and how it says, in addition to accounting for related publications, journalistic genres, location, graphic aids (E.A.G) and audiovisual aids (E.A.A). The techniques used were documentary review, content analysis (each with its matrix), and interviews with experts related to the topic. In this paper, we analyzed 88 publications from the four media studied. The results obtained allowed the researcher to identify the approach of each newspaper, one in favor, one against and two that, by the way they treated and presented the facts, they approached impartiality. Thus, the analysis of its contents, inclination, and mostly the way of processing information, was studied. Finally, as a proposal, a scientific article was written on the results obtained, which was sent to be published in a journal ranked in Scopus.